Paris in the Spotlight of Lithuania’s Provisional Capital: Round the Fountain, or a Little Paris by Markas Zingeris - Vaičiulėnaitė-Kašelionienė, Nijolė (Literatūra, 2016)
The paper aims to highlight the image of Paris in Markas Zingeris’ novel Aplink fontaną arba mažasis Paryžius (Around the Fountain or Little Paris) by applying a conjoined approach of comparative and imagological analysis. Particular attention is paid to analyzing the topos of Paris; for this analysis, Paul Ricoeur’s ‘circle of representation’ and Pierre Brunel’s rules for comparative method (‘three steps’ tactic) are applied. The origins of the signs of Paris thus come into light, together with the meanings they create within the space of the Other as the representations of the ‘great’ and the ‘little’ capitals collide; the possibilities of reading those signs become clear. While explaining the practice of ‘creative imagination’, the carnival poetics and the peculiarity of language are highlighted. Having assembled the materials of the research, the specifics of the image of Paris are revealed and the ’Little Paris’ phenomenon that Markas Zingleris created for Lithuanian culture is assessed.
Keywords: image; imagology; comparative; ideology; utopia